Effect of MnOx/TiO2 Oxidation State on Ozone Concentration in a Nonthermal Plasma-Driven Catalysis Reactor. (3rd March 2016) - Pangilinan, Christian David C.; Kurniawan, Winarto; Hinode, Hirofumi
ABSTRACT: Manganese oxides on titanium dioxide were prepared by impregnation method at various calcination temperatures and by deposition-precipitation method and the catalysts were characterized using TG-DTA, XRD, XPS, and N2 adsorption. Various oxidation states for manganese were obtained and activity towards ozone decomposition inside a nonthermal plasma catalysis reactor was investigated. Activity tests show that with increasing manganese oxidation state, the greater the degree of ozone decomposition inside the reactor. MnOx/TiO2 prepared by impregnation method calcined at 350 °C showed the highest decrease in ozone concentration.